Inhibiting the interaction between apoptosis-inducing factor and cyclophilin A prevents brain injury in neonatal mice after hypoxia-ischemia. (July 2020) - Rodriguez, Juan; Xie, Cuicui; Li, Tao; Sun, Yanyan; Wang, Yafeng; Xu, Yiran; Li, Kenan; Zhang, Shan; Zhou, Kai; Wang, Yong; Mallard, Carina; Hagberg, Henrik; et al.
Abstract: The interaction between apoptosis-inducing factor (AIF) and cyclophilin A (CypA) has been shown to contribute to caspase-independent apoptosis. Blocking the AIF/CypA interaction protects against glutamate-induced neuronal cell death in vitro, and the purpose of this study was to determine the in vivo effect of an AIF/CypA interaction blocking peptide (AIF(370-394)-TAT) on neonatal mouse brain injury after hypoxia-ischemia (HI). The pups were treated with AIF (370-394)-TAT peptide intranasally prior to HI. Brain injury was significantly reduced at 72 h after HI in the AIF(370-394)-TAT peptide treatment group compared to vehicle-only treatment for both the gray matter and the subcortical white matter, and the neuroprotection was more pronounced in males than in females. Neuronal cell death was evaluated in males at 8 h and 24 h post-HI, and it was decreased significantly in the CA1 region of the hippocampus and the nucleus habenularis region after AIF(370-394)-TAT treatment. Caspase-independent apoptosis was decreased in the cortex, striatum, and nucleus habenularis after AIF(370-394)-TAT treatment, but no significant change was found on caspase-dependent apoptosis as indicated by the number of active caspase-3-labeled cells. Further analysis showed that both AIF and CypA nuclear accumulation were decreased after treatment with the AIF(370-394)-TAT peptide. These results suggest that AIF(370-394)-TAT inhibited AIF/CypA translocation to the nucleus and reduced HI-induced caspase-independent apoptosis and brain injury in young male mice, suggesting that blocking AIF/CypA might be a potential therapeutic target for neonatal brain injury. Highlights: Apoptotic cell death is more prominent in the immature brain after insult. Apoptosis inducing factor (AIF) plays a crucial role in the process of apoptosis in the immature brain after injury. AIF induces apoptosis require interaction with cyclophilin A. Blocking interaction of AIF and cyclophilin A reduces caspase-independent cell death and brain injury only in males.